Long-term Monitoring of Low-cost Seismometers: Consistency Analysis of The Instrument - Juellyan, Juellyan; Hasan, Muttaqin; Achmad, Ashfa; Yulianur, Alfiansyah; Saidi, Taufiq; Setiawan, Bambang (Aceh International Journal of Science and Technology, 2024)
Instruments have become an essential part of conducting a study or research. With the aid of instruments, the measurement process can be faster, more efficient, and more accurate. However, an instrument also has a limited service life. Over time, the performance of the instrument will degrade. Therefore, the equipment must be regularly maintained and calibrated periodically. This research aims to test the measurement consistency of a low-cost seismometer (RS-3D). The approach involves long-term measurements to assess the instrument's stability in taking measurements. The measurement data is then processed and presented as frequencies using spectrum analysis. The research findings indicate that the instrument's consistency is generally good, with an average standard deviation of 0.18 and a coefficient of variation of 5%. Additionally, 95% confidence interval calculations yielded values of 2.520.02 for measurements at RKD, 3.040.05 for measurements at GLT-USK, and 3.30.04 for measurements at GFT-USK. Data validation was performed using the equations from building codes, showing that the difference between the measured microtremor frequency and the empirical equation was less than 1, indicating good measurement results. The conclusion drawn from this study is that a higher standard deviation value indicates a more distributed data spread, signifying less consistent research data. Conversely, a lower standard deviation indicates that the data is more concentrated around the mean value, indicating more consistent measurement results. Moreover, with previous studies having conducted validation and consistency testing, it is hoped that both tests will be routinely performed during instrument maintenance.